Nomophobia Sebagai Moderator Antara Kontrol Diri Terhadap Cyberslacking Pada Mahasiswa Selama Pembelajaran Daring - Aini, Luthfi Noor; Rinaldi, Martaria Rizky (Jurnal Online Psikogenesis, 2023)
Most of the students were found to be accessing the internet outside of academic interests while concurrent with online learning. The use of the internet that is not relevant to academic activities is called cyberslacking. This study aims to determine the moderating role of nomophobia on the relationship between self-control and cyberslacking behavior in students when carrying out online learning. This research is a quantitative research type, the research subjects were 105 student respondents. Data collection tools are self-control scale, nomopobhia scale and cyberslacking scale. Data analysis has been done with Moderated Regression Analysis technique. The results showed that self-control has a direct effect on cyberslacking, while nomophobia does not moderate the effect of self-control on cyberslacking.